2013
DOI: 10.4240/wjgs.v5.i3.27
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for arterial reconstruction in surgery for pancreatic cancer?

Abstract: Surgery remains the only potentially curative treatment for patients with pancreatic cancer. Locally advanced pancreatic cancer with vascular involvement remains a surgical challenge because high perioperative risk and the uncertainty of a survival benefit. Whilst portal vein resection has started to gather momentum because the perioperative morbidity and long term survival is comparable to standard pancreatectomy, there isn't yet a consensus on arterial resections. There have been various reports and case ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…1. The invasion of the common hepatic artery (CHA) or the gastroduodenal artery (GDA) at its origin, of the superior mesenteric artery (SMA), or the celiac axis (CA) is usually considered as a contraindication for resection due to the risks of both morbidity and mortality, and poor oncological results (56,(110)(111)(112)(113) The report from the French Association of Surgery (41) (2004-2009) showed that in France AR was performed during pancreatectomy for PDAC in 2% of cases (37/1670, 27 + VR) with a morbidity rate of 54%, a 30-day mortality rate of 8% and a 3-year survival rate of 8% (median: 12.7 months, median survival rate without recurrence, 7 months). In a VR study in this series, AR significantly increased mortality (RR = 2.09; 95% CI = 0.99-4.38; p = 0.05) (LE 4).…”
Section: Commentsmentioning
confidence: 99%
“…1. The invasion of the common hepatic artery (CHA) or the gastroduodenal artery (GDA) at its origin, of the superior mesenteric artery (SMA), or the celiac axis (CA) is usually considered as a contraindication for resection due to the risks of both morbidity and mortality, and poor oncological results (56,(110)(111)(112)(113) The report from the French Association of Surgery (41) (2004-2009) showed that in France AR was performed during pancreatectomy for PDAC in 2% of cases (37/1670, 27 + VR) with a morbidity rate of 54%, a 30-day mortality rate of 8% and a 3-year survival rate of 8% (median: 12.7 months, median survival rate without recurrence, 7 months). In a VR study in this series, AR significantly increased mortality (RR = 2.09; 95% CI = 0.99-4.38; p = 0.05) (LE 4).…”
Section: Commentsmentioning
confidence: 99%
“…Currently, surgical resection is considered the only possible curative approach for pancreatic tumors [13]. However, postsurgical outcomes remain poor as most patients present with advanced stage disease [4].…”
Section: Introductionmentioning
confidence: 99%
“… 2 4 VR is classified into four types: type 1 involves partial venous excision with direct closure, type 2 involves partial venous excision using a patch, type 3 involves segmental resection with primary venovenous anastomosis, and type 4 involves segmental resection with an interposed venous conduit. 5 In clinical practice, venous graft interposition following segmental resection of the PV/SMV remains only a small part of vascular reconstruction, 6 , 7 and the operative procedure, venous status, and long-term outcomes still require detailed evaluation. A recent report from the authors’ department presented a new venous reconstruction technique using the iliac vein harvested from donation after cardiac death (DCD) and addressed the feasibility of this method.…”
Section: Introductionmentioning
confidence: 99%